I'm having difficulty showing this equality (assuming that the question doesn't have a typo).. I've tried in both directions and I can't seem to get what I need.

\begin{align} A\setminus (B\setminus C)&=A\cap\overline{(B\cap \overline{C})}\\ &=A\cap(\overline{B}\cup C)\\ &=(A\cap \overline{B})\cup(A\cap C)\\ &=(A\setminus B)\cup (A\cap C) \end{align}

And in the other direction (A bit more convoluted):

\begin{align} (A\setminus B)\cup (A\cap B\cap C)&=(A\cap\overline{B})\cup(A\cap B\cap C)\\ &=[A\cup (A\cap \overline{B})]\cup [B\cup (A\cap \overline{B})]\cup [C\cup (A\cap \overline{B})]\\ &=[A\cup (A\cap \overline{B})]\cup [(B\cup A)\cap(B\cup\overline{B})]\cup [C\cup (A\cap \overline{B})]\\ &=[A\cup (A\cap \overline{B})]\cup [(B\cup A)\cap\mathcal{U}]\cup [C\cup (A\cap \overline{B})]\\ &=[A\cup (A\cap \overline{B})]\cup (B\cup A)\cup [C\cup (A\cap \overline{B})]\\ &=[(A\cap \overline{B})\cup (A\cap \overline{B})]\cup(A\cup A)\cup B\cup C\\ &=(A\setminus B)\cup A\cup B\cup C \end{align}

Both of these seem to be "close", but neither is the same, and neither quite get to the goal. Is there a flaw in my algebra? Or is this not even possible using this method?


Write $A\cap C = (A\cap B\cap C)\cup (A\cap \overline{B}\cap C)$ in the second-to-last last line of the first part:

$$\begin{align}A\setminus(B\setminus C)&=(A\cap \overline{B})\cup(A\cap C) =(A\cap \overline{B})\cup(A\cap \overline{B}\cap C)\cup(A\cap B\cap C) \end{align}$$

Then note that $$(A\cap \overline{B})\cup(A\cap \overline{B}\cap C)=A\cap \overline B.$$

You need $$X\cup (X\cap Y)= X\tag{1}$$$$X\cap(Y\cup\overline{Y})=X\tag{2}$$

You can prove (2) if you know that:

$$X\cup\overline{X} = Y\cup\overline{Y}\tag{3}$$ $$X\cap (X\cup Y)=X\tag{4}$$

Proof of $2$ using $3,4$:

$$X\cap (Y\cup \overline Y)=X\cap (X\cup \overline X) = X$$

  • $\begingroup$ I vaguely recall this from some years ago -- what is this property/equality/law called? I'm referring to the addition of $B$ and $\overline{B}$ to both sides of a union $\endgroup$ – agent154 Sep 19 '15 at 17:15
  • $\begingroup$ In general: $X = (X\cap B)\cup(X\cap \overline B)$. This follows because $X=X\cap (B\cup \overline{B})$, which is just saying that $B\cup\overline{B}$ is the entire universe. Not sure what that is called. $\endgroup$ – Thomas Andrews Sep 19 '15 at 17:19
  • $\begingroup$ The second equality is that $X\cup(X\cap B)=X$. Again, not sure what that is called. $\endgroup$ – Thomas Andrews Sep 19 '15 at 17:21

Hint: Using $^c$ to denote complement, $$ A\setminus\left(B\setminus C\right)=A\cap\left(B\cap C^{c}\right)^{c}=A\cap\left(B^{c}\cup C\right)=A\cap\left(B^{c}\cup\left(B\cap C\right)\right). $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.